2017
DOI: 10.1212/wnl.0000000000003809
|View full text |Cite
|
Sign up to set email alerts
|

Limited role for extended maintenance temozolomide for newly diagnosed glioblastoma

Abstract: This study provides Class III evidence that in patients with newly diagnosed glioblastoma, prolonged TMZ chemotherapy does not significantly increase PFS or OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
2
39
2
2
Order By: Relevance
“…Early publications on this subject claimed prolonged survival of patients receiving temozolomide treatment extended beyond 6 cycles [ 37 – 40 ]. In contrast, three recent interesting works concluded that continuing temozolomide beyond 6 cycles does not show longer OS [ 35 , 41 , 42 ]. But none of them was a specific clinical trial or a real population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Early publications on this subject claimed prolonged survival of patients receiving temozolomide treatment extended beyond 6 cycles [ 37 – 40 ]. In contrast, three recent interesting works concluded that continuing temozolomide beyond 6 cycles does not show longer OS [ 35 , 41 , 42 ]. But none of them was a specific clinical trial or a real population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the adaption of the schedule, for example, 21/28 days or 7/14 days temozolomide in the maintenance phase 32 , 33 nor the longer exposure 34 has a proven impact to date.…”
Section: Standard Of Carementioning
confidence: 99%
“…Even with advances in surgical procedures, radio-therapeutic technologies, and discovery of new chemotherapeutic agents such as bevacizumab (Avastin) ( 6 , 7 ), patients with GBM still have a dismal prognosis, which is approximately 19 months for median OS ( 8 ), although some reports showed 2-year survival rates of 40–50% ( 9 , 10 ) to date. Survival rates of patients with glioblastoma are relatively low, and the failure of treatments is mostly due to recurrence.…”
Section: Introductionmentioning
confidence: 99%